Soil Quality and Region Influence Performance and Ranking of Switchgrass Genotypes. Issue 1 (1st January 2019) - Casler, M. D.; Sosa, S.; Boe, A. R.; Bonos, S. A.
Abstract : Development of switchgrass ( Panicum virgatum L.) as a dedicated bioenergy feedstock requires intensive and extensive breeding programs that include careful and thoughtful consideration of appropriate target populations of environments (TPEs). The purpose of this study was to evaluate region (climate), soil quality, and N fertilization level as potential factors influencing the choice of TPE. A total of 45 switchgrass genotypes were evaluated in uniform field studies at six field sites defined as prime or marginal soils in New Jersey, South Dakota, and Wisconsin. Region and soil quality had strong interactions with genotype, but N fertilization had little impact on genetic variation or ranking of genotypes. Lowland genotypes were considerably more sensitive than upland genotypes to interactions with environmental factors, probably due to these field sites being outside of the traditional lowland adaptation zones. Genotype rankings were highly inconsistent across regions and soil types, indicating that breeding programs that target marginal soils should be located on soils that represent the appropriate TPE. Furthermore, interactions across the three regions suggest that breeding programs for the lowland ecotype should be subdivided into different sets of TPEs, which are largely a function of hardiness zone and annual precipitation. Lastly, even with negligible interactions involving N fertilization level, future definitions of TPEs should be based on minimal or no N fertilizer applications to allow breeders to select plants with greater N‐use efficiency, N‐scavenging ability, and N‐recycling efficiency.